L-Arginine Supplementation for Improving Pregnancy Outcomes - Ahmed Mohammed Zheoat; Alaa Ibraheem Lazim (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study evaluates the effects of L-Arginine supplementation on pregnancy outcomes, focusing on the incidence of preeclampsia, fetal outcomes, and maternal and neonatal safety. A total of 200 pregnant women were randomly assigned to either the intervention group, receiving L-Arginine supplementation, or a control group. The results revealed a significant reduction in the incidence of preeclampsia in the intervention group (15%) compared to the control group (28%), with a p-value of <0.01. Additionally, fetal outcomes were improved in the intervention group, with significantly higher birth weight (3150 ± 300 g vs. 2850 ± 280 g) and longer gestational age (39.5 ± 1.2 weeks vs. 38.0 ± 1.3 weeks) compared to the control group, both with p-values <0.05. Maternal and neonatal safety outcomes showed minimal differences between the two groups, with no significant increase in nausea, headache, or neonatal Apgar scores. These findings suggest that L-Arginine supplementation is an effective intervention for reducing the incidence of preeclampsia and improving fetal outcomes, while maintaining a favorable safety profile for both mother and child. Further studies are needed to confirm these results and explore the long-term benefits and optimal use of L-Arginine supplementation during pregnancy.